Genetic technology - Sabo, Linda; Faas, Lisa; Sourbeer, Dan (Biology: the fabric of life ;, 1999)
Explores topics in genetic technology, explaining how restriction enzymes are used and discussing probes, gel electrophoresis, steps in a DNA fingerprint, and uses for DNA fingerprinting